Evaluation of dynamic mechanical and cytotoxic properties of electrospun poly (lactic acid)/cellulose nanocrystalline composite membranes. Issue 1 (January 2021) - Wang, Fadong; Zhou, Mengjiao; Jia, Qingxiu
Abstract: In this paper, polylactic acid (PLA)/cellulose nanocrystalline (CNC) composite fiber membranes were prepared by electrospinning technique. The microstructure of the fiber membranes produced was all transformed from a smooth surface to a nanoporous surface by varying the CNC loading level. The influence of CNC content on the morphology, thermal dynamic properties, and cytotoxic properties of PLA/CNC composite nanofiber membranes was characterized. The results show that water molecules can enhance the hydrogen bonding networks between PLA and CNC. when the cellulose nanocrystal content is less than 10%, the composite membranes have good dynamic mechanical properties and no significant cytotoxic effect.